Annual Africa Partner Reports, Year 5. - Feed the Future Innovation Lab for Nutrition. (Tufts University. Tisch Library., 2016)
A compilation of the Nutrition Innovation Lab's partners' 2015 annual reports submitted USAID, honing in on their specific contributions to the Innovation Lab's projects, efforts, and outcomes. Partners include Harvard School of Public Health, Purdue University, Tuskegee University, Makerere University. Keywords: Annual Report, Stunting.; Nutrition School: Annual Reports.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy